Potential for knowledge managament and innovation ecosystem for aquaculture development - Faizan Hasan Mustafa (2017)
This thesis deals with potential of knowledge management and innovation ecosystem perspectives of seafood producing systems through aquaculture which have hitherto not received due attention. Now that seafood has assumed a growing importance as a means of ensuring food security, the role of aquaculture in the rapidly developing blue economy and its socio-economic benefits demands serious attention. The thesis explains that growth of this economic sector of fish farming not only requires development of technology and adoption of certain practices but also managing the knowledge that has accumulated. This thesis uses both primary and secondary data in order to achieve its three objectives, primary data has been collected in the form of Delphi methodology in which group of experts have been selected carefully in order to get sound results, secondary data has been gathered in the form of published articles and other internet sources, which establish that knowledge management and innovation ecosystems are much needed in aquaculture if aquaculture is to meet its production targets and achieve goal of sustainability, a framework has been established which consists of tools such as: K-Blogs, K-Café, K-Clusters, Peer Assist, Voice-and-Voip among others. These tools are not only effective in knowledge consolidation and diffusion but also in generation of new information that can be used for finding practical solutions to technical problems, especially through aquaculture incubators. Using some of these tools, a model of an economically feasible ‘smart fish farming system’ was designed for controlling the main parameters of water quality to ensure sustainability of these essential components of the farming system. Despite complexity in evolving this system, the application is simple enough to be operated by an organized fish farming community, particularly the medium and large enterprises. A section of the thesis exclusively deals with transformation of aquaculture research through innovation ecosystem. This topic provides a structured framework for creating ingredients that constitute an environment (termed as innovation ecosystem) that encourages innovations to address specific problems in fish farming so the industry could grow to ensure seafood supplies to the market at affordable price. The main elements of this are interdisciplinary, multidisciplinary and transdisciplinary research that looks into the problems from all the possible angles, and developing a workable platform for interaction among academia, traditional fish farming community and the industry. Regarding the third objective of this thesis which is to identify aquaculture systems and provide synergies between the two, an aquaculture model has been prepared using tilapia, where data has been collected on various aspects of fish biology as well as its marketing, the output of the model states that with 1% mortality rate found in university model shows profit as compared with the industry model where mortality rate is 50%. Two distinct models of farming systems identified in this study are: the knowledge-based University Model and the more business-oriented Industry Model. Their differences are borne out of the cultural divide between a university and an industry.